Shelf-life evaluation and nutraceutical properties of chia seeds from a recent long-day flowering genotype cultivated in Mediterranean area. (January 2018) - Caruso, M.C.; Favati, F.; Di Cairano, M.; Galgano, F.; Labella, R.; Scarpa, T.; Condelli, N.
Abstract: Chia seeds ( S. hispanica L.) are a good source of nutrients like essential fatty acids, fiber and antioxidant compounds; for this reason they are considered as functional foods. Chia seeds are usually cultivated in Central America, while a few reports about their growing outside of this area are reported. In this paper seeds obtained from a recent G8 genotype, a long-day flowering line of chia, grown in Mediterranean area have been analyzed during storage time to evaluate their oxidative stability and nutraceutical compounds. Seeds were grown with two different levels of irrigation and two levels of sowing density. No significant influence of these factors on chemical composition of seeds has been found. Seed yield was comparable with the one from native area as well as fatty acid composition and antioxidant compounds content, even if a higher content of peroxides and a shorter predicted shelf life was recorded. Highlights: Chia seeds grown in Italy are qualitatively comparable to the ones grown in native areas. Chia seeds present an high content of antioxidant compounds. Sowing density and irrigation did not significantly influence the seed composition. Chia seeds composition varies significantly during storage time.